SISTEM PENUNJANG KEPUTUSAN UNTUK MENENTUKAN CAT TERLARIS PADA TOKO PLAZA BANGUNAN ASOKA - yanti yusman; Sri Haryati Haryati (Jurnal Teknovasi : Jurnal Teknik dan Inovasi, 2020)
Many ways can be used in determining the best-selling paint selection criteria in the Ashoka building plaza with the use of a decision support system so that it makes it easier for leaders to determine the type of paint that is in high demand by consumers by using a selection method that makes it easy to obtain information on a system built to manage data- data so as to provide convenience to users and can produce clear and accurate information and can produce reports that are expected to help leaders, and employees at the ASOKA BUILDING PLAZA Padang in making and making the right decisions later